Advanced manufacturing processes for the production of biosensors - Newman, Jeff D. (Cranfield University, 1998)
Biosensors were first described over thirty five years ago, but commercialisation did not occur until the early 1970s. Interest was subsequently sparked by the market for large numbers of disposable devices required for self-testing of blood glucose levels by diabetic patients. The introduction of automated production technology, for the manufacture of the millions of devices required, became a necessity. Screen printing has been the most successful of these technologies to date, but there are many other techniques which could be applicable to biosensor production. This thesis reviews the main technologies used in sensor construction and describes the manufacture of some devices using a range of these processes. The construction of transducers and subsequent chemically- and biologically-sensitive layers, as well as membrane structures are considered. Most of the work presented here concerns the manufacture of electrochemical devices, but many of the techniques described would be equally applicable to certain aspects of the production of other classes of biosensors.
Keywords: Self-testing; disposable; devices; diabetes; transducers; chemically sensitive; biologically sensitive